The influence of specific cognitive training in virtual reality on the inhibition of elite young ice hockey players - Heilmann, Florian; Schubert, Torsten (Frontiers in Sports and Active Living, 2025)
IntroductionExecutive functions (EFs) such as inhibition skills are crucial in sports, particularly in game sports, as they facilitate rapid decision-making, impulse control, and effective reactions to unforeseen situations. This study investigates the influence of specific cognitive training (CT) in virtual reality (VR) on inhibition in young ice hockey players compared to an individual technical training session. The potential implications of this research are significant, as it could lead to the development of new training methods to improve sports performance.MethodsThe study involved 25 young ice hockey players (5 female, Mdn: 14 years, span: 11–17 years). Before and after the training period, the test subjects completed sport-specific and general tests to measure inhibition ability (Go/No go task, Flanker task, sport-specific modified using a special measuring station). The intervention group (N = 12) engaged in sport-specific CT in virtual reality (2 times/week; 9 weeks), and the control group (N = 13) completed individual technique training.ResultsFor the Cued GoNoGo task, no significant main effects could be determined for the specific and non-specific tests (reaction time, accuracy). For the flanker task, significant main effects were found for the sport-specific test for the congruent (pre-post: p < .001; int.: p < .001; group: p = .112) and incongruent (pre-post: p < .001; int.: p < .001; group: p = .105) but not for the flanker effect (pre-post: p = .364; int.: p < .526; group: p = .597).DiscussionThe results show significant improvements in the flanker task for the intervention group in the sport-specific test for congruent and incongruent conditions. This suggests that CT in VR can potentially improve sport-specific inhibition skills in young ice hockey players, particularly in relation to dealing with distracting stimuli or distractors (flanker task). There were no prominent effects for domain-generic cognition tasks. Further research is needed to understand the long-term effects and the transferability of these training effects on ice hockey performance.